Experimental facility IHEPNP for fundamental and applied researhes in energy range up to 100 MeV - Ganenko, V.B.; Kasilov, V.I.; Kovalenko, G.D.; Maslov, N.I.; Semisalov, I.L. (Вопросы атомной науки и техники, 2020)
The possibility of creating an experimental setup in building No.3 of the IHEPNP NNC KIPT (LUE-300 complex) on the basis of the existing LUE-60 electron accelerator and the existing experimental infrastructure is being discussed. It is planned to raise the energy of the electron beam to 100 MeV and create two beam lines: one is for reaserches with intense beams of electrons and photons, including linearly polarized ones, and the other – for investigations with the low intensive beams of electrons and positrons. Implementation of the project will open opportunities for a wide range of research programs in the field of interaction of the radiation with amorphous and crystalline matter, nuclear physics and astrophysics, as well as in the applied research.